EVALUATION OF GAMMA RADIATION INDUCED MORPHOLOGICAL MUTANTS IN DOLICHOS BEAN ( ANTS IN DOLICHOS BEAN (Lablab Purpureus Purpureus L.) IN M2 GENERATION - HARISH KUMAR; S. M. GHAWADE; SHIVAPUTRA (The Bioscan, 2018)
The mutagenic sensitivity was evaluated in dolichos bean cultivars Deepali and Konkan Bushan by treating the seeds with 25kR, 35kR, 45kR, 55kR and 65kR of gamma radiations. All the treatments of both cultivars with gamma radiations had shown tremendous variations in morphological and yield traits in both the generations. In M1 generation, treatments with 65kR had registered the lowest germination (62% in Deepali and 59% in Konkan Bhushan) and the LD50 was reported 51.2kR and 48.6kR in Deepali and Konkan Bhushan respectively. In M2 generation mutagenic frequency, efficiency and effectiveness were increased with increasing doses of gamma radiations. The maximum frequency (19.72% in Deepali and 26.31% in Konkan Bhushan) was observed in 55 kR of both cultivars. Total 28 macromutants from Deepali and 37 macromutants from Konkan Bhushan were isolated. Among them the mutant having specific and beneficial traits from Deepali viz., dwarf (55kR) and small pod (45kR) mutants and Konkan Bhushan viz., dwarf (45kR and 55kR), extensive branching (55kR), early flowering (35kR and 55kR) and rachis branching (55kR) mutants were found useful and may be useful in breeding for further improvement of dolichos bean.